2016
DOI: 10.1111/jhq.12082
|View full text |Cite
|
Sign up to set email alerts
|

Family Physicians’ Quality Interventions and Performance Improvement for Hypertension through Maintenance of Certification

Abstract: Family physicians improved the quality of care for patients with hypertension through MOC. Leveraging MOC across all specialties may become an important support for improving management of conditions that cause considerable morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…Two training strategies will be tested (see Table 1), both increasingly used with PCPs, and developed in accordance with principles of adult leaning (59)(60)(61)(62)(63)(64). First, SEEK Maintenance of Certi cation (MOC-4) is an example of a structured Quality Improvement (QI) project approved by the American Boards of Pediatrics and of Family Medicine, required of physicians to maintain Board certi cation.…”
Section: Preliminary Effectiveness Of Seekmentioning
confidence: 99%
See 1 more Smart Citation
“…Two training strategies will be tested (see Table 1), both increasingly used with PCPs, and developed in accordance with principles of adult leaning (59)(60)(61)(62)(63)(64). First, SEEK Maintenance of Certi cation (MOC-4) is an example of a structured Quality Improvement (QI) project approved by the American Boards of Pediatrics and of Family Medicine, required of physicians to maintain Board certi cation.…”
Section: Preliminary Effectiveness Of Seekmentioning
confidence: 99%
“…Doing so will advance knowledge in implementation science related to primary care and the prevention of CM. The randomized Type III hybrid design (66) leverages a commitment by 5 major healthcare systems to implement SEEK, enabling a rigorous evaluation of implementation strategies to optimize the adoption and delivery of SEEK in primary care settings, and subsequent prevention of CM: the independent online (IND) (59-61) versus in-depth structured MOC training (62)(63)(64). We will also observe the impact of using the SEEKonline and the Traditional approach to guide delity of model delivery.…”
Section: Aimsmentioning
confidence: 99%
“…45,46 Six studies list the number of participating centers or practices (N = 157). One report was from the National Improvement Partnership Network, which consisted of 15 statewide QI partnerships at the time of the report.…”
Section: The Impact Of Qi Activities For Which Moc Credit Is Awardedmentioning
confidence: 99%
“…Several studies have shown no difference in outcomes for patients cared for by internists with ABIM time-limited vs time-unlimited certifi cates across a panel of ten primary care performance measures [ 21 ], and no difference in ambulatory care-sensitive hospitalizations when comparing internists with ABIM time-unlimited and time-limited certifi cates [ 22 ], though there was a small reduction in the growth differences of costs for a cohort of Medicare benefi ciaries [ 22 ]. Diplomates of American Board of Family Medicine ( ABFM ) who completed Performance in Practice modules related to hypertension showed improvement in most quality measures evaluated; however, though most had chosen lipid control as their quality improvement focus, no improvement was seen for that particular measure [ 23 ]. A similarly designed study evaluating ABFM diplomates ' performance in diabetes care showed that while all physician and patient quality measures improved, no consistent association was seen between improvement and processes of care when comparing physicians with time-limited vs time-unlimited certifi cates [ 24 ].…”
Section: Is the Moc Program Performing As It Should?mentioning
confidence: 99%